Electron beams and loss cones in the auroral regions of Jupiter. Issue 14 (27th July 2017) - Allegrini, F.; Bagenal, F.; Bolton, S.; Connerney, J.; Clark, G.; Ebert, R. W.; Kim, T. K.; Kurth, W. S.; Levin, S.; Louarn, P.; Mauk, B.; McComas, D. J.; et al.
Abstract: We report on the first observations of 100 eV to 100 keV electrons over the auroral regions of Jupiter by the Jovian Auroral Distributions Experiment (JADE) on board the Juno mission. The focus is on the regions that were magnetically connected to the main auroral oval. Amongst the most remarkable features, JADE observed electron beams, mostly upward going but also some downward going in the south, at latitudes from 69° to 72° and −66° to −70° corresponding to M shells ("M" for magnetic) from 18 to 54 and 28 to 61, respectively. The beams were replaced by upward loss cones at lower latitudes. There was no evidence of strongly accelerated downward electrons analogous to the auroral "inverted Vs" at Earth. Rather, the presence of upward loss cones suggests a diffuse aurora process. The energy spectra resemble tails of distributions or power laws (suggestive of a stochastic acceleration process) but can also have some clear enhancements or even peaks generally between 1 and 10 keV. Electron intensities change on timescales of a second or less at times implying that auroral structures can be of the order of a few tens of kilometers. Key Points: First 100 eV to 100 keV electron measurements in the auroral regions of Jupiter Upward and downward electron beams observed in the polar regions and on field lines connected to the middle plasma sheet Upward loss cone on the field lines connected to the inner plasma sheet suggesting a diffuse aurora process